2020
DOI: 10.2139/ssrn.3664995
|View full text |Cite
|
Sign up to set email alerts
|

Nudging Enforcers: How Norm Perceptions and Motives for Lying Shape Sanctions

Abstract: The enforcement of social norms is the fabric of a functioning society. Through the lens of two experiments, we examine how motives for lying and norm perceptions steer enforcement. Our contribution is to investigate the extent to which norm breaches are sanctioned, how normnudges affect the observed punishment behavior, and how the enforcement is linked to norm perceptions. Using a representative U.S. sample, Experiment 1 provides robust evidence that norm-enforcement is not only sensitive to the extent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 111 publications
1
11
0
Order By: Relevance
“…In fact, we found that the monthly income change was positively associated with the donation amount. Similar to previous findings (Bolton & Ockenfels, 2000; Dimant & Gesche, 2020; Fehr & Schmidt, 1999), these results imply that participants were generally concerned about disadvantageous inequality. In contrast, the interaction term between the income change and the norm‐breaker treatment was insignificant and negative (Table 3).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In fact, we found that the monthly income change was positively associated with the donation amount. Similar to previous findings (Bolton & Ockenfels, 2000; Dimant & Gesche, 2020; Fehr & Schmidt, 1999), these results imply that participants were generally concerned about disadvantageous inequality. In contrast, the interaction term between the income change and the norm‐breaker treatment was insignificant and negative (Table 3).…”
Section: Discussionsupporting
confidence: 90%
“…We believe that the present findings contribute to the empirical literature on the effect of social norms on behavior. Existing research mainly focuses on a particular norm, for example, lying (Dimant & Gesche, 2020), expressing xenophobic views (Bursztyn, Egorov, & Fiorin, 2020), and tax evasion (Dulleck et al., 2016; Hallsworth et al., 2017). However, our findings imply that people's behavior, including punishment toward norm‐breakers, can be affected by their perception of different types of norms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We argue that swiftness can serve as a useful tool for policy makers to design more efficient and/or potentially also less expensive institutional deterrence mechanisms. Naturally, the concepts of decision-making 1 Recent scholarly contributions have broadened this perspective and emphasized the importance of institutional structures, including staff rotations in the public administration, whistleblower protection, the bite of audits and formal punishment, and use of norm-nudge interventions (Shleifer & Vishny, 1993;Abbink, 2004;Nikiforakis, 2008;Sutter et al, 2010;Serra, 2011;Balafoutas & Nikiforakis, 2012;Abbink et al, 2014;Khadjavi, 2014;Engel et al, 2016;Buckenmaier et al, 2018;Bicchieri & Dimant, 2019;Hajikhameneh & Rubin, 2019;Dimant & Gesche, 2020). 2 Classically, celerity referred exclusively to the temporal delay of a potential sanction following a transgression.…”
Section: Introductionmentioning
confidence: 99%